2015
DOI: 10.1186/s12903-015-0064-0
|View full text |Cite
|
Sign up to set email alerts
|

The adequacy of lymph node harvest in concomitant neck block dissection and submental island flap reconstruction for oral squamous cell carcinoma; a case series from a single Egyptian institution

Abstract: BackgroundSquamous cell carcinoma (SCC) is a fairly common tumor of the oral cavity. This tumor may affect any part of the mucosa of the oral cavity especially the tongue, the floor of the mouth and lips. The encountered intra-oral defects after tumor resection are often large and require climbing up the reconstruction ladder to more complex reconstructive options for accepted functional and cosmetic results to be achieved. However, most of the patients are old with medical co-morbidities requiring fast, simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 22 publications
2
10
0
1
Order By: Relevance
“…More recently, the flap was been used for oral cavity and oropharyngeal mucosal defects. The oncologic safety and adequacy of lymph node dissection has been demonstrated by multiple groups . The oncologic safety is less of a concern in the management of oropharyngeal, laryngeal, and hypopharyngeal compared with oral cavity tumors.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the flap was been used for oral cavity and oropharyngeal mucosal defects. The oncologic safety and adequacy of lymph node dissection has been demonstrated by multiple groups . The oncologic safety is less of a concern in the management of oropharyngeal, laryngeal, and hypopharyngeal compared with oral cavity tumors.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been used for malar augmentation with fascia flap only, 29,32 reconstruction of defects with hair-bearing skin, 33 tongue and/or floor of mouth defects, buccal mucosa defects, palatal defects, 34 nasal reconstruction, 35 lip reconstruction, [36][37][38] cervical esophagus repair or reconstruction, [39][40][41] hemilaryngectomy defects repair, 31 reconstruction of the neopharynx after total laryngectomy, repair of pharyngocutaneous fistulas 42 and coverage of hardware used in spine surgery. 43 There is controversy in the literature about the oncological safety of the SAIF due to the relationship between the flap and lymph nodes of the Ib region, because these nodal levels might be involved even at an early stage of OSCC, 44,45 and this can increase the risk of recurrence, 44,46,47 as well as hindering a rigorous cervical level I neck dissection.…”
Section: Discussionmentioning
confidence: 99%
“…For the primary parotid cancer, level 1A nodal disease is an atypical presentation, as compared to oral cavity. In the case of oral cavity tumors, several studies have demonstrated safety with using the submental flap . In 50 patients with oral cavity malignancies undergoing submental flap reconstruction, Howard et al demonstrated occult nodal disease in level 1A in 10% of patients, without compromise to the patient's cancer care in using this flap .…”
Section: Discussionmentioning
confidence: 99%